Transportation of micro-polar fluid by dilating peristaltic waves - Sanjay Kumar Pandey; Subhash Chandra (Journal of King Saud University: Science, 2020)
In this paper, we analytically investigate axi-symmetric flow of a micro-polar fluid induced by peristaltic waves with progressively dilating amplitude. By means of mathematical formulation we examine its impact on swallowing of single food bolus through oesophagus. Liquid crystals, blood, some edible solutions resemble micro-polar property. Engineering applications using polymer solutions, colloidal solutions, drilling fluids in oil industries etc. may be better understood by this investigation. Long wavelength and low Reynolds number approximations are employed to get rid of non-linear convective terms and minimise curvature effects of the wall. It is inferred that increasing coupling number and amplitude dilation parameter enhance the pressure inside the tube, while micro-polar parameter is responsible for reducing the pressure along the axis of the tube. Local wall shear stress too increases with amplitude dilation parameter. The study suggests that achalasia patients should avoid the consuption of micro-polar fluids. It is also concluded that reflux action weakens with dilation of wave amplitude for micro-polar flows.